CONNECTION OF DWELLING QUALITY WITH THE SOCIAL-ECONOMIC FEATURES OF THE PEOPLE LIVING IN IT - O. V. Grigoryeva; N. S. Grigoryeva (Russian Journal of Economics and Law, 2013)
Objective: To study the social-economic features of people living in different categories of houses. Methods: Complete survey of respondents, building and comparing the mean weighted quantities and average-linear deflection were used, as well as analysis, synthesis and abstract-logical method. Results: Basing on the analysis of the collected empirical data, it is revealed that economic, social and demographic characteristics of population significantly differ depending on the quality of dwelling where the live. The dwelling fund structure is determined. The steady social-economic trend is revealed to acquire dwelling real estate in compliance with income and social position. Scientific novelty: The method of researching the dwelling fund structure is proposed, reflecting the general economic trends of changing the population’s quality of living. Categories of houses are determined. Dependence of welfare on educational level, social position and character of labor activity is revealed. Practical value: Possibility to obtain data on the modern condition of dwelling fund, and its changes during transitional period. It allows to estimate the demand for new dwellings and reveal categories of persons on which the programs of state support in the dwelling sphere should be aimed.